Analysis of Pollution Levels of Heavy Metals of Lead (Pb) And Copper (Cu) In Freshwater Fish In Lake Toba Water - Pane, Eva Pratiwi; Siahaan, Fine Eirene (Universitas Pendidikan Ganesha, 2023)
Community activities in an effort to utilize the wealth of Lake Toba water resources can produce heavy metals in the waters and affect the life of biota that interact directly with the waters, especially freshwater fish. This research aims to analyzez the concentration of heavy metals contained in freshwater fish in the waters of Lake Toba. The research was conducted in August-September 2022 in the waters of Lake Toba, Simalungun Regency, North Sumatra Province. The sampling process used purposive sampling method. Data analysis was carried out descriptively by looking at the results of measurements of several water parameters and the results of sample tests in the laboratory by comparing the quality standards. The results of the concentration of heavy metals contained in freshwater fish for Pb ranged from 0.0386 to 0.0700 ppm while for Cu metal ranged from 0.0059 to 0.0325 ppm. The results of the calculation of the value of the bioconcentration factor (BCF) of freshwater fish on Pb metal ranged from 0.401 to 0.721 while the value of the bioconcentration factor (BCF) of Cu metal ranged from 2.347 to 8.325. Analysis of the effect of the relationship between heavy metal content in plankton on environmental parameters processed using SPSS 16 software, showed that there was a fairly close relationship between heavy metals Pb and Cu in freshwater fish which was influenced by water parameters in Lake Toba. Environmental parameters that affect the content of heavy metals in freshwater fish include temperature, current velocity, salinity, dissolved oxygen and pH.